Growth Performance and Expression of Immune-Regulatory Genes in Rainbow Trout (Oncorhynchus Mykiss) Juveniles Fed Extruded Diets with Varying Levels of Lupin (Lupinus Albus), Peas (Pisum Sativum) and Rapeseed (Brassica Napus) - Cofre-Montenegro, C; Vidal-Soto, R (2013)
Sin Editorial Disponible